2023
DOI: 10.1109/tdsc.2022.3156941
|View full text |Cite
|
Sign up to set email alerts
|

RGB Cameras Failures and Their Effects in Autonomous Driving Applications

Abstract: RGB cameras are one of the most relevant sensors for autonomous driving applications. It is undeniable that failures of vehicle cameras may compromise the autonomous driving task, possibly leading to unsafe behaviors when images that are subsequently processed by the driving system are altered. To support the definition of safe and robust vehicle architectures and intelligent systems, in this paper we define the failure modes of a vehicle camera, together with an analysis of effects and known mitigations. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 60 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…The most comprehensive work on visual camera failures is [22], where the authors systematically identified the failure modes and effects of a visual camera through the application of a Failure Mode and Effects Analysis (FMEA). The effects of camera failures on the output images are summarized in Fig.…”
Section: Background On Visual Camera Failuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The most comprehensive work on visual camera failures is [22], where the authors systematically identified the failure modes and effects of a visual camera through the application of a Failure Mode and Effects Analysis (FMEA). The effects of camera failures on the output images are summarized in Fig.…”
Section: Background On Visual Camera Failuresmentioning
confidence: 99%
“…multitude of reasons [32]: this paper accounts for possible failures of the visual camera, which may be due to internal (e.g., failures of the electrical parts), external (e.g., dirt or scratched lenses), or environmental (e.g., rain or icing on lenses) factors. We consider a complete set of visual camera failures resulting from a Failure Mode and Effect Analysis [22] to embrace a complete set of visual camera failures known to date, according to the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we consider faults in the three cameras used in the autonomous vehicle in our case study (discussed in the experiments section). While many types of faults can be associated with a digital camera, we focus on the common fault of occlusion [5]. We train a monitor using prior data and only use inference on the trained models at decision time.…”
Section: Runtime Monitorsmentioning
confidence: 99%
“…In recent years, depth cameras have been widely utilized in various fields, such as autonomous driving [1][2][3], robot grasping [4][5][6], and simultaneous localization and mapping (SLAM) [7][8][9]. However, due to object material, specular reflection, or occlusion, the captured depth data often exhibits holes at the edges where objects come into contact with the background.…”
Section: Introductionmentioning
confidence: 99%